Money - Burns, Peggy (Hove Wayland, 1994)
"Money" by Peggy Burns, published in 1994. This 32-page hardcover book is part of the "Stepping Through History" series and provides an overview of the history of money, from the bartering system to the complex money markets of today. The book includes both color and black-and-white illustrations to enhance understanding. ARCHIVE.ORG Given its publication date, the book provides historical context up to the early 1990s. For more recent information on the history of money, additional sources would be beneficial.